Pathways to Reducing Poverty and Sharing Prosperity in India : Schemes to Systems - Lessons from Social Protection in India - World Bank (World Bank, Washington, DC, 2020)
The changing nature of work is upending traditional employment globally, and with it, social protection systems. As countries like India aspire to grow further and navigate a phase of rapid economic transformation, investments in social protection programs are critical to ensure broad gains for societies in general, and the poorest in particular. The series of articles take stock of India’s major social protection programs, including pension programs, health insurance, the public distribution system, and the Mahatma Gandhi National Rural Employment Guarantee Scheme. The latter two are among the largest anti-poverty measures in India and indeed the world, while the former are relatively new instruments for unorganized workers. However, these programs are important for India’s future social policy architecture as they attempt to de-link social security benefits from a person’s place of work. The final two articles draw on experiences from the past decade to highlight how best to use information technology to strengthen the capability of governments to design and implement social protection programs.